2004
DOI: 10.1074/jbc.m405150200
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis DesR Functions as a Phosphorylation-activated Switch to Control Membrane Lipid Fluidity

Abstract: The Des pathway of Bacillus subtilis regulates the synthesis of the cold-shock induced membrane-bound enzyme ⌬5-fatty acid desaturase (⌬5-Des). A central component of the Des pathway is the response regulator, DesR, which is activated by a membrane-associated kinase, DesK, in response to a decrease in membrane lipid fluidity. Despite genetic and biochemical studies, specific details of the interaction between DesR and the DNA remain unknown. In this study we show that only the phosphorylated form of protein De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 33 publications
1
61
0
Order By: Relevance
“…In the cyanobacterium genus Synechocystis, the expression of three desaturases (encoded by desA, desB, and desD) is inducible under cold temperatures. The sensor/signal pathway for regulation of transcription of the single desaturase found in Bacillus subtillus, encoded by des, has also been thoroughly investigated (35,142).…”
Section: Membrane Lipid Compositionmentioning
confidence: 99%
“…In the cyanobacterium genus Synechocystis, the expression of three desaturases (encoded by desA, desB, and desD) is inducible under cold temperatures. The sensor/signal pathway for regulation of transcription of the single desaturase found in Bacillus subtillus, encoded by des, has also been thoroughly investigated (35,142).…”
Section: Membrane Lipid Compositionmentioning
confidence: 99%
“…In bacteria, membrane fluidity is mostly regulated by adapting the length and saturation of acyl chains (3). For instance, upon lowering of the growth temperature, bacteria will typically increase the content of unsaturated acyl chains, shorten chain length, and modify branching or cyclization to lower the temperature of phase transition from gel to liquid-crystalline state, a process called homeoviscous adaptation (4).…”
mentioning
confidence: 99%
“…Several lines of evidence show that the cold thermal stimulus is detected by DesK, which together with the response regulator (RR), DesR, constitutes a canonical two-component system (TCS). In vivo experiments have demonstrated that DesK acts as a kinase at cold temperatures (4), ultimately activating the transcription of the gene des coding for the acyl lipid desaturase ⌬5-Des (1,5). The increased fraction of unsaturated fatty acids in the membrane then restores fluidity and shuts off the kinase activity of DesK, terminating transcription.…”
mentioning
confidence: 99%